Advances in the pathogenesis of psoriasis: from keratinocyte perspective - Zhou, Xue; Chen, Youdong; Cui, Lian; Shi, Yuling; Guo, Chunyuan (Cell death & disease, 2022)
Psoriasis is a complex long-lasting inflammatory skin disease with high prevalence and associated comorbidity. It is characterized by epidermal hyperplasia and dermal infiltration of immune cells. Here, we review the role of keratinocytes in the pathogenesis of psoriasis, focusing on factors relevant to genetics, cytokines and receptors, metabolism, cell signaling, transcription factors, non-coding RNAs, antimicrobial peptides, and proteins with other different functions. The critical role of keratinocytes in initiating and maintaining the inflammatory state suggests the great significance of targeting keratinocytes for the treatment of psoriasis.